Virgil’s Dido and the Death of Marcus Antonius - Fratantuono, Lee (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Virgil’s account of the death of Dido at the end of Aeneid IV has been the subject of an appreciably extensive critical bibliography. What has not been recognized to date has been the influence of the tradition of the suicide of the former triumvir Marcus Antonius on Virgil’s depiction of Dido’s demise.